Presence of Two Separate Hairy Polyps with Meningothelial Elements in a 15-Month-Old Child - Ahmad Saeed A. Alghamdi; Nasser Almutairi; Ghassan Alokby (Case Reports in Otolaryngology)
Hairy polyps are benign embryological tumors of the head and neck region that are derived from two germinal layers, the ectoderm and mesoderm. At an incidence of 1 : 40000, hairy polyps are considered rare growths. Presenting symptoms of hairy polyps can vary greatly depending on the size and location of the tumor. To the best of our knowledge, our reported case is the first in the literature to highlight an extremely rare occurrence of two separate hairy polyps being simultaneously present in one patient, in the clivus and the nasion, with the presence of meningothelial cells within both tumors, histopathologically. With surgical resection as the management of choice, the approach of surgery differs greatly depending on many factors. Since the patient in our reported case had a cleft palate, we used a combined transnasal and transoral approach to fully release the clival mass and a direct skin incision for the nasion mass. Recurrence after complete surgical resection is rare, and if happens, it should rise suspicion of histopathologically misdiagnosed tumor. We amplified the importance of advanced radiological investigations along with proper multidisciplinary teamwork to exclude CNS connections and other histologically malignant tumors and to early pick up a possible simultaneous lesion.